Mitochondrial Mutations in Ethambutol-Induced Optic Neuropathy - Zhang, Xiao-Hui; Xie, Yue; Xu, Quan-Gang; Cao, Kai; Xu, Ke; Jin, Zi-Bing; Li, Yang; Wei, Shi-Hui (Frontiers in Cell and Developmental Biology, 2021)
Background: Ethambutol-induced optic neuropathy (EON) is a well-recognized ocular complication in patients who take ethambutol as a tuberculosis treatment. The aim of the current study was to investigate the presence of mitochondrial mutations, including OPA1 and Leber’s hereditary optic neuropathy (LHON)-mitochondrial DNA (mtDNA), in patients with EON and to determine their effect on clinical features of these patients. Methods: All 47 patients underwent clinical evaluations, including best-corrected visual acuity, fundus examination, and color fundus photography; 37 patients were then followed up over time. Molecular screening methods, including PCR-based sequencing of the OPA1 gene and LHON-mtDNA mutations, together with targeted exome sequencing, were used to detect mutations. Results: We detected 15 OPA1 mutations in 18 patients and two LHON-mtDNA mutations in four patients, for an overall mutation detection rate of 46.8%. The mean presentation age was significantly younger in the patients with the mitochondrial mutations (27.5 years) than in those without mutations (48 years). Fundus examination revealed a greater prevalence of optic disc hyperemia in the patients with mutations (70.5%) than without mutations (48%). Half of the patients with mutations and 91% of the patients without mutations had improved vision. After adjusting for confounders, the logistic regression revealed that the patients with optic disc pallor on the first visit (p=0.004) or the patients with the mitochondrial mutations (p<0.001) had a poorer vision prognosis. Conclusion: Our results indicated that carriers with OPA1 mutations might be more vulnerable for the toxicity of EMB to develop EON.